INTEGRATING ACEH LOCAL WISDOM THROUGH THE E-STAR MODEL TO STRENGTHEN ELEMENTARY STUDENTS’ SCIENCE LITERACY - Rahma Rahma; M Solehuddin (Universitas HKBP Nommensen, 2026)
This study aims to develop and test the effectiveness of the E-STAR (Ethno-STEAM Assisted by Augmented Reality) model, which integrates Acehnese local wisdom into science learning on the Water Cycle and Weather Phenomena for fifth-grade elementary school students in Lhokseumawe City. The study used a quasi-experimental design with a nonequivalent control group design. The subjects were 60 fifth-grade students from two public elementary schools in Lhokseumawe City. Data collection instruments included a science literacy test, an observation sheet on learning implementation, and a student response questionnaire. Data analysis used an independent t-test and an N-Gain test. The results showed that the E-STAR model had a significant effect on strengthening students' science literacy (p < 0.05), with an average N-Gain of 0.72 (high category) for the experimental class compared to 0.38 (medium category) for the control class. The integration of Acehnese local wisdom, such as the concept of pantan melarang (prohibition) related to water management, and the expression hana ka, i.e., hana ka ureueng, in water cycle learning was proven to be able to improve the contextualization of materials and students' learning motivation. AR visualization supports concrete conceptual understanding of weather phenomena. This study concludes that the E-STAR model is an effective, innovative learning model for improving elementary school students' scientific literacy.